2017
DOI: 10.1039/c7ee01109a
|View full text |Cite
|
Sign up to set email alerts
|

Linker-controlled polymeric photocatalyst for highly efficient hydrogen evolution from water

Abstract: A linker-controlled strategy has been demonstrated to synthesize polymeric photocatalysts for efficient H2 evolution by UV-Vis-IR with benchmark quantum yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
161
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 243 publications
(174 citation statements)
references
References 68 publications
13
161
0
Order By: Relevance
“…6,8,16,17 For polymer based photocatalysts, up to now, there are many reports about proton reduction by either g-C 3 N 4 or g-C 3 N 4 doped by oxygen, boron, phosphorus, etc. 6,9,[18][19][20][21] For example, Wang et al reported that graphitic carbon nitride presents great potential for photocatalytic proton reduction in 2009 and platinum decorated g-C 3 N 4 shows ca. 10 mmol h À1 hydrogen evolution rate under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,8,16,17 For polymer based photocatalysts, up to now, there are many reports about proton reduction by either g-C 3 N 4 or g-C 3 N 4 doped by oxygen, boron, phosphorus, etc. 6,9,[18][19][20][21] For example, Wang et al reported that graphitic carbon nitride presents great potential for photocatalytic proton reduction in 2009 and platinum decorated g-C 3 N 4 shows ca. 10 mmol h À1 hydrogen evolution rate under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…18 Later, the light absorbance of this polymer was extended to 800 nm by controlling the linker of carbon nitride and it generated H 2 by light irradiation from the ultraviolet to near infrared regions. 9 This progress in polymer photocatalysts for proton reduction has played a crucial role to stimulate research interest in polymer photocatalysts. However, the most challenging step, water oxidation, in water splitting has met with little success in polymer photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations